Geological characteristics of biogenic gas formation and direction of favorable zones in the Quaternary mudstone of the Qaidam Basin, China - Jixian Tian; Zeyu Shao; Jian Li; Dekang Song; Zhou Fei; Ya'nan Li; Wei Sha; Hao Zhang; Lili Hou; Xiaoqiu Zhang; Haining Zhang; Yixuan Yang (Journal of Natural Gas Geoscience)
Quaternary biogas is the main natural gas resource in the Qaidam Basin, where sandstone reservoirs have traditionally been the primary producers. However, reserve growth in these reservoirs has become increasingly difficult in recent years. Mudstone gas, representing a new exploration field, has a low exploration level, and its formation, reservoir characteristics, and potential remain unknown. In this study, we utilize core data from the mudstone sections of two newly drilled wells in the study area as the object, and carry out a comprehensive study of the formation and reservoir characteristics of mudstone biogas through systematic experimental analysis, on the basis of which, favourable exploration areas for mudstone biogas are identified. The results of the study show that: (1) The Quaternary mudstone is mainly composed of dark grey mudstone in shallow and semi-deep lake, and influenced by the anoxic environment of brackish water and semi-brine water, exhibiting blocky, striped, and laminar structures. The mudstone layers frequently feature interbeds of sand and carbonate rocks. in which the mudstone is mainly concentrated in the Ⅲ, Ⅵ, and Ⅷ layer groups, characterized by large thickness and good continuity. (2) The low abundance of organic matter in the Quaternary mudstone, but a substantial proportion of organic matter suitable for microbial modification, and the large amount of different types of organic matter, such as hydrocarbons and algae, improve the biogas gas production capacity of the Quaternary system. (3) The Quaternary mudstone exhibits various pore types, including primary intergranular pores, dissolution pores, cracks, and a small number of organic pores. It is characterized by high porosity and permeability, although the pore radii of macropores, mesopores, and micropores are relatively small. (4) On-site analysis shows that mudstone layers are generally gas-bearing, with free gas being the main gas. Gas accumulation is prominent in brittle mineral developmental zones and tectonic high points within gas-bearing sections. (5) The loose Quaternary mudstone, with its high porosity and permeability, is controlled by various factors such as water content, overburden pressure, and mudstone thickness, and has the ability of self-containment and self-sealing properties. It is concluded that the Quaternary mudstone gas reservoir follows a formation model characterized by “integrated source and storage, brittle mineral content-controlled accumulation, mudstone thickness and pore sealing, and tectonic direction control”. Favorable areas for mudstone gas accumulation include the three major fields and the northern slope of the study area.